2017
DOI: 10.1038/s41598-017-08985-w
|View full text |Cite
|
Sign up to set email alerts
|

The Multi Domain Caldicellulosiruptor bescii CelA Cellulase Excels at the Hydrolysis of Crystalline Cellulose

Abstract: The crystalline nature of cellulose microfibrils is one of the key factors influencing biomass recalcitrance which is a key technical and economic barrier to overcome to make cellulosic biofuels a commercial reality. To date, all known fungal enzymes tested have great difficulty degrading highly crystalline cellulosic substrates. We have demonstrated that the CelA cellulase from Caldicellulosiruptor bescii degrades highly crystalline cellulose as well as low crystallinity substrates making it the only known ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
2
45
0
Order By: Relevance
“…The performance of the hyperthermophilic CelA enzyme from C. bescii has recently been reported to be agnostic to the crystalline content of cellulose, converting high crystallinity cotton linters (66% CI) cellulose at the same rate as low crystallinity cotton linters cellulose (33% CI). 2 To determine if the colocalization of exo-and endocellulase activity domains could Multifunctional enzyme performance data (A) multifunctional enzyme digestions of crystalline Avicel substrate, Cel7A-CBM3b-Cel5A (red), Cel7A-CBM1-Cel5A ( purple), Cel7A-Link-Cel5A (green), Cel7A + Cel5A (orange), Cel7A (blue) (B) Avicel digestion comparing a Cel7A with native CBM1 (blue) versus a Cel7A with a CBM3b attached (red). (C) High and low crystallinity cotton linter digest, Cel7A-CBM3b-Cel5A 66% crystalline material ( pink), Cel7A-CBM3b-Cel5A 33% crystalline material (red), Cel7A-CBM1-Cel5A 66% crystalline material (light purple) Cel7A-CBM1-Cel5A 33% crystalline material ( purple) (D) multifunctional supplemented enzyme digestions of DDR substrate, Cel7A-CBM3b-Cel5A + Ctec2 (red), Cel7A-CBM1-Cel5A + Ctec2 ( purple), Cel7A-Link-Cel5A + Ctec2 (green), Cel7a + Cel5A + Ctec2 (blue).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the hyperthermophilic CelA enzyme from C. bescii has recently been reported to be agnostic to the crystalline content of cellulose, converting high crystallinity cotton linters (66% CI) cellulose at the same rate as low crystallinity cotton linters cellulose (33% CI). 2 To determine if the colocalization of exo-and endocellulase activity domains could Multifunctional enzyme performance data (A) multifunctional enzyme digestions of crystalline Avicel substrate, Cel7A-CBM3b-Cel5A (red), Cel7A-CBM1-Cel5A ( purple), Cel7A-Link-Cel5A (green), Cel7A + Cel5A (orange), Cel7A (blue) (B) Avicel digestion comparing a Cel7A with native CBM1 (blue) versus a Cel7A with a CBM3b attached (red). (C) High and low crystallinity cotton linter digest, Cel7A-CBM3b-Cel5A 66% crystalline material ( pink), Cel7A-CBM3b-Cel5A 33% crystalline material (red), Cel7A-CBM1-Cel5A 66% crystalline material (light purple) Cel7A-CBM1-Cel5A 33% crystalline material ( purple) (D) multifunctional supplemented enzyme digestions of DDR substrate, Cel7A-CBM3b-Cel5A + Ctec2 (red), Cel7A-CBM1-Cel5A + Ctec2 ( purple), Cel7A-Link-Cel5A + Ctec2 (green), Cel7a + Cel5A + Ctec2 (blue).…”
Section: Resultsmentioning
confidence: 99%
“…Multifunctional cellulolytic enzymes, such as CelA from Caldicellulosiruptor bescii, [1][2][3] represent a novel intermediate class of biomass deconstructing enzymesfalling between the well-known free enzyme systems found in most fungi and bacteria and the highly complexed, bacterial cellulosome systems produced by microbes such as Clostridium thermocellum. [4][5][6] The extremely high cellulolytic activity, unique pit-forming mechanism, and recently reported cellulose crystallinity-agnostic behavior of CelA makes it a very important enzyme to investigate further.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Caldicellulosiruptor carbohydrate-active enzymes (CAZymes [8]) are also modular, consisting of combinations of catalytic and noncatalytic (e.g., carbohydrate binding module [CBM]) domains connected by proline/threonine-rich linkers in various arrangements. The best-studied example is the multifunctional cellulase CelA, which is arranged as GH9-CBM3-CBM3-CBM3-GH48 domains, where the numbers refer to specific protein families (9)(10)(11)(12)(13)(14)(15). The synergy between the endoglucanase (GH9) and exoglucanase (GH48) domains contributes to a novel mode of action for CelA that involves physically burrowing into cellulose fibers, thereby creating cavities for further enzymatic access to the carbohydrate content of plant biomass (9).…”
mentioning
confidence: 99%
“…As a result, big breakthroughs in biomass conversion have been made. For example, POET-DSM claimed that a bottleneck in their pretreatment technology was resolved by enhanced enzymatic digestion of feedstocks [2], the National Renewable Energy Laboratory found that CelA cellulase from Caldicellulosiruptor bescii could efficiently hydrolyze cellulose with a high degree of crystallinity [3], and Nguyen et al demonstrated a great improvement of ethanol titer (86 g/L) and low enzyme dosage (~ 6.5 filter paper unit g glucan −1 ) by combining a cosolvent-enhanced lignocellulosic fractionation pretreatment strategy with simultaneous saccharification and fermentation [4]. As such, while well-recognized technical barriers to viable commercialization of cellulosic ethanol are overcome, the fermentation process itself is now identified as a limiting factor; with current techniques limited by relatively low productivity and intensive labor.…”
Section: Introductionmentioning
confidence: 99%